DIAGNOSTIC CHALLENGE IN DISTINGUISHING BENIGN FROM RARE MALIGNANT UTERINE PATHOLOGY – A CASE REPORT OF A MYXOID LEIOMYOSARCOMA - Dimitrov, Goran; Tofiloska, Valentina; Dzikova, Elena; Gjoreski, Josif; Biljan, Aleksandra (SHMSHM - AAMD, 2023)
Leiomyosarcomas are rare aggressive soft tissue tumors, which account for 1 to 2% of all uterine malignancies. Due to their infrequency, as well as the difficulty to distinguish them from leiomyomas, the diagnosis is often made postoperatively. We report a case of a 38-year-old patient who was treated at the University Clinic for Obstetrics and Gynecology – Skopje for an enlarging uterine fibroid, for which she had undergone a myomectomy. The histopathology report showed that it was a case of a myxoid leiomyosarcoma, FIGO Stage IB, involving margins. She was admitted for a reoperation which consisted of a total hysterectomy, bilateral adnexectomy, selective lymphadenectomy and staging. The final postoperative clinical stage was FIGO IB. Leiomyosarcomas are generally less responsive to chemotherapy or radiation, most often have a poor prognosis and a high risk of recurrence. Surgery is the most significant treatment modality. The prognosis primarily depends on the FIGO stage, as the most important independent variable associated with survival.
Keywords: leiomyosarcoma; sarcoma; rare; uterus; uterine malignancy